2015
DOI: 10.1080/08975930.2014.929513
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Business Classes Abroad: How International Experience Benefits Faculty, Students, and Institutions

Abstract: International educational experiences can provide benefits for faculty members as well as higher education institutions and their students. The opportunity to lecture and conduct research with colleagues at universities in other countries can foster the globalization or internationalization of academic teaching, the advancement of knowledge, and cooperation among institutions. Research has shown that the experience abroad helps educators to gain a more global perspective that will enhance business classes. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Faculty members' prior international experience/intercultural competence was another notable area of difference among the goals of the faculty members in our survey. The study abroad literature points to the importance of considering faculty members' own intercultural competence as a predictor of their approaches to teaching abroad (e.g., Goode, 2008;Miglietti, 2015;Paige & Goode, 2009); and we found some limited, but nuanced, support for this assertion. Although we did not have a direct measure of intercultural competence, which may have led to different conclusions, we did not find two variables that are likely to be related to intercultural competence -speaking multiple languages and being born outside of the U.S. -to be significantly related to faculty members' goals.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Faculty members' prior international experience/intercultural competence was another notable area of difference among the goals of the faculty members in our survey. The study abroad literature points to the importance of considering faculty members' own intercultural competence as a predictor of their approaches to teaching abroad (e.g., Goode, 2008;Miglietti, 2015;Paige & Goode, 2009); and we found some limited, but nuanced, support for this assertion. Although we did not have a direct measure of intercultural competence, which may have led to different conclusions, we did not find two variables that are likely to be related to intercultural competence -speaking multiple languages and being born outside of the U.S. -to be significantly related to faculty members' goals.…”
Section: Discussionsupporting
confidence: 49%
“…In a recent study of short-term study abroad course instructors, Niehaus, Reading, Nelson, Wegener and Arthur (2018) found rank, gender, race, discipline, and prior international travel experiences to be significant predictors of the extent to which faculty members engaged in various forms of cultural mentoring while teaching abroad. Other researchers have identified the importance of faculty members' prior experience, particularly prior international experience, in shaping their own intercultural competence and thus their approach to facilitating students' intercultural development (e.g., Goode, 2008;Miglietti, 2015;Paige & Goode, 2009). Discipline may be particularly important in understanding goals for short-term study abroad because faculty members' disciplinary training and socialization in some fields may lead them to emphasize disciplinary content over reflection, experience, and intercultural learning (Lutterman-Aguilar & Gignerich, 2002).…”
Section: The Importance Of the Facultymentioning
confidence: 99%
“…As Schlein and Garii (2011) explained, educators can use international experiences to become "culturally enhanced" (p. 82) and bring these enhancements back to their classrooms and back to their colleagues. In her study of business faculty who participated in an international educational experience, Miglietti (2015) found that they changed their teaching by increasing the global content of their classes.…”
Section: Discussionmentioning
confidence: 99%
“…Some universities have faculty exchange programs which provide benefits for faculties as well as their universities. An opportunity to lecture in another university is an invaluable experience [35]. Experience abroad helps faculty members enhance their understanding of global issues.…”
Section: Faculty Exchange Programsmentioning
confidence: 99%